Corporate foresight towards a maturity model for the future orientation of a firm - Rohrbeck, René; SpringerLink (Online resource). (Heidelberg Physica-Verlag HD, 2011)
Have you ever wondered why even large companies fail when faced with changes in their environment? Would you be surprised to learn that the average life expectancy of a Fortune 500 company is below 50 years? This book presents findings from 19 case studies in multinational companies such as Siemens, Volkwagen, General Electric, Philips and Deutsche Telekom. René Rohrbeck proposes a Maturity Model to assess how prepared a company is to respond to external (disruptive) change. He uses data from 107 interviews with board members, corporate strategists, innovation managers, and corporate foresight professionals to present and discuss best practices. Using illustrations to show the complex interaction of corporate foresight with other units such as innovation and strategic management, René Rohrbeck provides the reader with rich insights on how to make an organization agile and reactive towards change. For scholars this book proposes multiple hypotheses and frameworks for future research."Both the model and practice examples contained within make the book a worthwhile reference for companies seeking to enhance their ability to succeed in a changing environment." Peter Möckel and Heinrich Arnold of Deutsche Telekom Laboratories."His maturity model and the identified best practices contribute to both strategic management and innovation management theory and will help pave the way toward a better understanding of how companies can build "dynamic capabilities". Hans Georg Gemünden of Technische Universität Berlin."The thesis of Rene´ Rohrbeck on Corporate Foresight will help managers create an understanding about its breadth and depth; they will learn to know what to expect from their investments and to judge the effectiveness of their Corporate Foresight practices. Martin G. Möhrle of University of Bremen."With this book, the author opens new perspectives, contributes valuable empirical evidence, and generates important new insights, which will take research and management practice in Corporate Foresight to a new level." Ulrich Krystek of Technische Universitä
Introduction. Literature Review. Research Design -- The Maturity Model of Corporate Foresight -- Best-practices in corporate foresight. Discussion and Conclusion. References.Appendix
Electronic reproduction.
Keywords: Management; Structural adjustment (Economic policy)